Plants in child care in Ahmednagar district, Maharashtra (India) - Mulay, J R; Sharma, P P (Recent Research in Science and Technology, 2012)
The present ethno-botanical explorations conducted in forest areas of Ahmednagar district resulted in the information about traditional plant uses of 47 plants species belonging to 30 Angiospermic families. Of these, maximum species belongs to Euphorbiaceae with 5 species, 3 species to Fabaceae and Solanaceae each. Information gathered from district indicates that the tribals, and other village people of this region possess good knowledge of herbal drugs for treating diseases of their children, but their continuous and progressive exposure to modernization may result in extinction of the such rich heritage of knowledge in the course of time. Diseases / ailments found prevalent in the area are skin diseases, respiratory diseases, tooch ache, fever, liver disorders and wounds.